Transparent bacterial cellulose nanocomposites used as substrate for organic light-emitting diodes - Legnani, Cristiano; Barud, Hernane S.; Caiut, José M. A.; Calil, Vanessa L.; Maciel, Indhira O.; Quirino, Welber G.; Ribeiro, Sidney J. L. [UNESP]; Cremona, Marco (Springer Nature, 2019)
In this work, high transparent bacterial cellulose (HTBC) biocompatible membranes were produced to be used as substrates in organic light-emitting diodes (OLEDs). These multifunctional membranes are based on bacterial cellulose (BC) and an organic–inorganic sol, composed of boehmite (Boe) nanoparticles and epoxi modified siloxane (GTPS). In order to be used as substrates, BC/Boe-GPTS membranes were covered with silicon dioxide (SiO 2 ) and indium tin oxide (ITO) thin films deposited at room temperature using radio frequency (RF) magnetron sputtering. Visible light transmission improves to 88%, instead of 40% previously achieved. The electrical properties for HTBC/SiO 2 /ITO substrate shows that the ITO deposited films are n-type doped semiconductors with resistivity of 2.7 × 10 −4  Ω cm, carrier concentration of − 1.48 × 10 21  cm −3 , and mobility of 15.2 cm 2  V −1  s −1 . These values are comparable to those of commercial ITO deposited onto glass substrates. After the characterization of the HTBC film, we used it as a substrate for the fabrication of a small molecule organic light-emitting diode OLED. The maximum efficiencies obtained were 1.95 cd/A and 1.68 cd/A for the reference OLED and the HTBC OLED, respectively. The HTBC OLED efficiency is then around 86% of the standard ITO-based OLED. This is clearly a good improvement, since previous BC-based simple architecture devices without Boe-GPTS have an efficiency 50% smaller than that of the standard OLED.